Idiopathic inflammatory myopathies: Contributions from India - Anand Narayan Malaviya (Indian Journal of Rheumatology)
A careful literature search would reveal significant contributions by Indian clinicians and basic researchers in the field of Idiopathic inflammatory myopathies (IIMs). The main drug used for its treatment, methotrexate (MTX), was synthesized for the first time by an Indian biochemist Yella Pragada Subbarow, working in New York (1948). Its first use for treating IIM patients was also by an Indian physician working in Boston (1968), Anand Narayan Malaviya. Similarly, there are several publications on the different aspects of the disease from India. Although the publications in the 1980s and 1990s were only a few and far between, starting early in this millennium, the pace of publications rapidly picked up. From the early purely clinical-observation-based papers, the area of research that has been covered in more recent papers has become much wider. Epidemiology, different age groups, unusual presentations, mimics of IIM, treatments being used and response to treatments, histoimmunopathological studies, studies of myositis-specific antibodies, basic immunological research in IIM, genetic studies, are now being published frequently. In this 'Introductory' paper, a time-line summary of the Indian contribution in the IIM research from India has been provided.